Persepsi Mahasiswa Terhadap Tahap Persiapan Bedside Teaching Pada Pembelajaran Rotasi Klinik - Nindya Aryanty; Ananda Ulandari (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2013)
ABSTRACT Background: Bedside teaching is an integral process of medical education. It will run effectively if only the preparation process prepared well. Preseptor need to comprehend curriculum in order to formulate purpose and theme in learning activity. Patient and setting for bedside teaching also need to be arranged carefully. As for student, preceptor needs to motivate them to occupy themselves with knowledge and clinical skills related to the bedside theme. Objectives: This research aim to evaluate bedside teaching preparation based on student perception. Methods: This descriptive study purposively involved 81 interns who were conducting learning at internal medicine, obstetric-gynecology, pediatric, and surgery department by the time of data collection performed. Questioner consists of 6 items to describe bedside teaching preparation phase (Corrected Item Total correlation > 0,3; Alpha Cronbach’s 0,826) was delivered among all respondents. Results: 66.7% respondents perceived that bedside teaching was not well prepared. Some students admit that preseptor do not always inform them about the theme, learning objective, and which patient that will involve in bedside teaching. Some of them also answer that they were not instructed to prepare themselves with knowledge and skills needed for bedside teaching. Conclusion: Institution needs to facilitate training to maximize preceptor comprehension to conduct well prepared bedside teaching. Keywords : preparation, bedside teaching